A Novel Technique for Epidermal Morphology of Leaf - Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2010)
The article describes a novel technique for morphological study of leaf epidermis in the field condition. Epidermal study provides a basis for taxonomic interrelationship of larger groups such as family. It helps in identification and differentiation of crop cultivars/varieties. The technique is referred to as epidermal peeling. It can directly be done on leaf or stem of plant. This easy to do method involves application of sticky solution of thermocol dissolved in xylene on leaf surface, semi-drying of solution, pressing of transparent cellophane tape on it, and pasting of cellophane on slide for observing epidermal tissue system under microscope. The method is scientific, easy to handle, and quick; helps to observe epidermis with stomata in natural open state without damaging structure; and useful for studying stomatal conductivity and gaseous exchange including the study of stomatal index, trichome density as well as density of glands and crystals.